Light environment in the understory of an Andean cloud forest: canopy structure and climatic seasonality - Quevedo Rojas, Ana Mercedes; Schwarzkopf, Teresa; García, Carlos; Jerez Rico, Mauricio (Revista de Biología Tropical, 2016)
The light environment in the understory of cloud forests is highly heterogeneous and determined by species composition, canopy structure, site conditions, and seasonality. This study was carried out at San Eusebio cloud forest, Venezuela (2 300 - 2 500 masl). The impact of canopy structure variations on understory light availability was estimated in the dry (December-February) and rainy (March-November) seasons, in sites under continuous canopy cover and gaps of various sizes. Hemispherical photographs were taken to estimate the percentage of canopy openness, leaf area index, percentages of transmitted direct and diffuse light, and duration and frequency of sunflecks. A light index was calculated from the relative proportions of direct and diffuse light transmitted to the understory. For most variables, there were significant differences between seasons, as well as among different gap sizes and under closed canopy. The light index was low (0.25 to 26 of a maximum = 100), even for the largest gaps, indicating a highly shaded light environment, especially beneath closed canopy in the rainy season. Patterns and interactions among factors were analyzed (gaps vs. continuous canopy, gap sizes, location within the gaps, and seasonality) with a mixed effects repeated measures Anova design. Results showed that the amount of light reaching the understory is low in both gaps and closed canopy. However, small but significant differences in light availability existed for both seasonality and magnitude of the perturbations. These differences could contribute to explain the dynamics of tree species regeneration in this forest. The knowledge of the factors conditioning light availability in the understory where tree regeneration begins is crucial in cloud forests because of energetic limitations in this ecosystem, and might be essential for future restoration and conservation plans concerning the preservation of the diversity and integrity of these forests.